Non-contact Human Body Measuring Technology Based on Camera Calibration Technique (Journal of Fiber Bioengineering and Informatics, 2015)
The basic theory of camera calibration is firstly introduced in this paper. The model of camera distortion\ris put forward. And discussed the parameters and the calibration process of the mathematical model of\r3D human body reconstruction. In the process of camera calibration, an improved algorithm based on\rthe two steps is proposed. This method has low requirements on experimental. This method has low\rrequirement to experiment, and only with coplanar points to calibrate. By the process of fractional step\rcalibration, the nonlinear equation is linear, which is beneficial to improve the calibration accuracy.
Keywords: Non-contact Human Body Measurement; Camera Calibration; The Radial Distortion; Non-linear Model